Occurrence of Covid-19 in Children Who Have Received Live-Attenuated Dengue Vaccination - Rahma Karyanti, Mulya; Alam , Anggraini; Widyahening , Indah Suci; Hadinegoro, Sri Rezeki; Munasir , Zakiudin; Sasmono , R. Tedjo; Satari , Hindra Irawan (Proceedings Book of International Conference and Exhibition on The Indonesian Medical Education Research Institute, 2023)
Background: Possible cross-reactions/ false positives were reported in rapid dengue serology tests because antigenic similarities between SARS-CoV-2 and DENV. The study aims to evaluate the occurrence of COVID-19 in children who received chimeric-yellow fever tetravalent dengue vaccine. Methods: A case-control study was conducted in five districts primary healthcares in Jakarta aged 12 years and above through history of COVID-19 questionnaire. Clinical and laboratory confirmation were obtained, and blood draw was performed to measure neutralization RBD IgG SARS-CoV-2 antibody titer. The dengue vaccine group consists of subjects who have received CYD-TDV in 2011-2012 and are willing to participate. The non-dengue vaccine group were matched; all have not received dengue vaccine. Results: This study included 207 cases and 212 controls, with median age in cases 19 years (IQR 5) and control 15 years (IQR 4). Nineteen subjects in the dengue vaccine group have already been infected with COVID-19 before being given COVID-19 vaccine, compared to 11 subjects in the non-dengue vaccine group (P=0.131). The occurrence of COVID-19 in the dengue vaccine group was significantly higher (16 subjects) than the non-dengue vaccine group (4 subjects)(P=0.005) after COVID-19 vaccinations were given. Neutralization RBD IgG SARS-CoV-2 antibody titer was 71.96 U/ml (IQR 39.47) in the dengue vaccine group and 51.92 U/ml (IQR 49.03) in the non-dengue vaccine group(P=0.361). Conclusion: Our study showed that the occurrence of COVID-19 in the dengue vaccine group was higher than in the non-dengue vaccine group, which may suggest no cross reaction from dengue antibodies towards COVID-19, more studies are warranted.